Brief Motivational Intervention for Substance Use may Decrease Violence Among Heavy Alcohol Users in a Jail Diversion Program - Catterall, Imogen (Criminal justice and behavior, 2021)
Rates of harmful alcohol use are high among justice-involved individuals and may contribute to violent recidivism. Robust treatments for alcohol-related violence in criminal justice systems are thus a public health priority. In this analysis of existing randomized controlled trial data (N = 105), we examined the impact of a brief motivational intervention (BMI) for harmful substance use on violent recidivism among individuals in a pretrial jail diversion program. Results indicated that, after controlling for violence history, the intervention’s impact on violent recidivism was moderated by baseline harmful alcohol use. Specifically, among people with severe alcohol problems at baseline, the BMI + standard care group had less violent recidivism at a 1-year follow-up than participants randomized to standard care alone. This finding was unchanged when we accounted for psychopathic traits. Our study provides preliminary evidence that a BMI may be useful for decreasing violent recidivism among heavy drinkers in criminal justice systems.